Research on impact of alternating air flow on quality of vibro-frictional separation of fine-seed materials (Science journal «Technical service of agriculture, forestry and transport systems», 2026)
Achieving precise separation by a single criterion for fine-seed crops is challenging due to the similarity in the variation series of characteristics across different fractions. To attain the desired effect, complex separation methods must be applied, which increases the cost of the final product due to the low productivity of separators, increased resource usage, and seed damage from multiple processing cycles. This issue is addressed by adding symmetrical working blocks so that the blocks are positioned above and below the vibrator. When the number of surfaces in the blocks is equally increased, the center of mass of the vibrating table remains unchanged. The oscillation identity is preserved, and the machine's productivity increases.The alternating air flow affects the dynamics of seed movement relative to the working surfaces under vibration. For seeds that are rounded and relatively large and dense, the air flow impact on the separation process is negligible. However, for seeds with pronounced aerodynamic properties and relatively low mass, the air flow has a significant effect. In some cases, this impact can practically eliminate the directed vibrational movement of the seed material, resulting in low separation efficiency for such types of seed material.Studies have shown that the function of the impact of alternating air flow on the quality of vibro-frictional seed separation does not exhibit a distinct extremum. Therefore, the selection of optimal design and operational parameters is recommended at the boundary of their existence. To reduce the impact of alternating air flow on the quality of vibro-separation of seed material, the use of an aerodynamic screen with a vertical wall height of 100-110% and a distance from the edge of 50-65% of the existing vertical gap between the working surfaces of the block is recommended. Considering these parameters, the formulated practical recommendations can enhance the efficiency of vibro-frictional separation of fine-seed crop materials
Keywords: seeds; vibro-frictional separation; extremum; separation efficiency; movement dynamic; alternating air flow; aerodynamic screen